Underground personnel and equipment location system based on iBeacon technology - ZHANG Hang; SUN Xiaoyu; TIAN Fengliang (Gong-kuang zidonghua, 2016)
In order to solve the positioning problem of underground personnel and equipment, positioning principles and algorithms of iBeacon indoor positioning technology were deeply analyzed, and a design scheme of underground personnel and equipment location system based on iBeacon technology was put forward. At the same time, the system architecture, beacon layout, mobile App development were introduced. Applying iBeacon technology to underground personnel and equipment positioning has advantages of high positioning precision, easy deployment and quick navigation.